Financial inclusion of rural households in the mobile money era: insights from Ghana. Issue 1 (2nd January 2022) - Serbeh, Richard; Adjei, Prince Osei-Wusu; Forkuor, David
ABSTRACT: This paper explores the financial inclusion prospects of mobile money by drawing on the experiences of rural households in the Sunyani West District of Ghana. By employing a qualitative approach, we argue that the suitability of mobile money to financial inclusion in rural areas has a checquered outlook. This is because although the platform ensures ease, nearness, and speedy transaction, digital illiteracy, irregular service delivery, and poor network connectivity question the goodness of fit between mobile money and the rural environment. While mobile money provided transfer and savings services, the persistence of these constraints negatively influenced these financial inclusion potentials.